Design of event-triggered state estimator with unknown input in wireless sensor networks - Cheng-han XIE; Sai-jie LU; Yun-ji LI; Li PENG (Tongxin xuebao)
With the development of sensors and wireless network technology,a series of new applications based on the wireless sensor has been merged in the past decades.Too much energy consumption and over-abundant occupancy rates of bandwidth are great challenges in these new applications,thus,it is of great practical significance to study the energy saving of the data transmission among these nodes.An estimator with the corresponding event-triggered transmission scheme was investigated for a class of discrete-time stochastic systems subject to unknown input.Its features satisfied the characteristic of unbiased and minimum variance was designed and then the proposed event-triggered strategy,which decided the transfer time of the data packet,can be used to reduce the number of data transmission.Furthermore,an upper bound of system performance was derived for obtaining the parameters of event scheme in details.Finally,a numerical example was given to verify the potential and effectiveness of the proposed theoretical result.